(untitled) (Prostor, 2024)
Each geographic location has its own unique architectural language and characteristics. Therefore, it is important to acknowledge that architectural design cannot be universally suitable for every geography. To be able to think, calculate, evaluate and analyse all these and more at every scale is possible with ‘human-space relationship and psychology’ (HSRP). For this reason, HSRP seems to be a lerning necessity for architecture students, especially interior architecture departments, in undergraduate education processes. The study started by determining the position of architecture and interior architecture education and HSRP in undergraduate education. Based on the findings obtained and analysed, an education model on HSRP was developed and applied to interior architecture and architecture undergraduate students in three different academic terms. The HSRP education model combined theoretical subjects and activities, and the students’ cognitive levels were measured at the beginning and end of the academic term. Quantitative data demonstrated that the developed education model made the subject more comprehensible to the students compared to a purely theoretical approach. This emphasised the importance and necessity of the course.